Concurrent use of indacaterol plus tiotropium in patients with COPD provides superior bronchodilation compared with tiotropium alone: a randomised, double-blind comparison. Issue 9 (27th April 2012) - Mahler, Donald A; D'Urzo, Anthony; Bateman, Eric D; Özkan, Serir A; White, Tracy; Peckitt, Clare; Lassen, Cheryl; Kramer, Benjamin; ,
Abstract : Background: Current guidelines recommend treatment with one or more long-acting bronchodilators for patients with moderate or more severe chronic obstructive pulmonary disease (COPD). The authors investigated the approach of dual bronchodilation using indacaterol, a once-daily long-acting β2 agonist, and the long-acting muscarinic antagonist tiotropium, compared with tiotropium alone. Methods: In two identically designed, double-blind, 12-week studies, patients with moderate to severe COPD were randomised to indacaterol 150 μg once daily or matching placebo. All patients concurrently received open-label tiotropium 18 μg once daily. The primary outcome was standardised area under the curve of forced expiratory volume in 1 s (FEV1 ) from 5 min to 8 h post dose at week 12. The key secondary outcome was 24 h post-dose ('trough') FEV1 at week 12. Resting inspiratory capacity (IC) was measured in a subgroup. Results: 1134 and 1142 patients were randomised in studies 1 and 2; 94% and 94% completed. Compared with monotherapy, concurrent therapy increased FEV1 (area under the curve by 130 and 120 ml, trough by 80 and 70 ml; all p<0.001) and trough IC (by 130 and 100 ml, p<0.01). Cough was more common with indacaterol plus tiotropium (10% and 9%) than with tiotropium alone (4% and 4%). Most cases (∼90%) of cough were mild. Other adverse events were similar for the treatment groups. Conclusions: Compared with tiotropium monotherapy, indacaterol plus tiotropium provided greater bronchodilation and lung deflation (reflected by increased resting IC). Adverse events were similar between treatments apart from mild cough being more common with indacaterol plus tiotropium. These results support COPD guideline recommendations to combine bronchodilators with different mechanisms of action. Trial registration numbers: NCT00846586 and NCT00877383 .